Pengaruh Mobilisasi Dini Pasien Pasca Operasi Abdomen Terhadap Penyembuhan Luka dan Fungsi Pernafasan: Effect of Early Mobilization of Postoperative Abdominal Patients On Wound Healing and Respiratory Function - Reni Prima Gusty (NERS Jurnal Keperawatan, 2011)
Injury and pain resulted from surgery makes the patient too lazy to move so delays wound healing and leads respiratory complications mobilization is a prominent factor in accelerating wound healing and optimal postoperative respiratory function. Type of research is Quasi-experimental approach to posttest control group design. Research objectives were to determine the effect of early mobilization after abdominal surgery on wound healing and respiratory function. Sample were 40 patients who undergone abdominal surgery room in IRNA RSUP DR. M. Djamil Padang. Analysis using Mann Whitney test. The results showed there were significant differences in wound healing and respiratory function of patients with postoperative abdominal between groups that do not perform according to the procedure of early mobilization (control) with early mobilization group that according to the procedure (treatment) for major surgery with p = 0.000. There were no significant differences in respiratory function of patients post abdominal surgery between the control group with treatment for minor surgery with p = 0.067 and there were significant differences in wound healing of the patient post abdominal surgery between the control group with treatment for minor surgery with p = 0.000. Hospital is expected to provide facilities to the smooth extension of early mobilization after surgery and nurses implements early mobilization in nursing care plan for recovery wound and increase respiratory function.